ON LACUNARY STATISTICAL BOUNDEDNESS OF ORDER ? - Et, Mikail; Mohiuddine, Syed A.; Sengul, Hacer (Univ Nis, 2016)
The aim of this paper is to introduce and examine the concept of lacunary statistical boundedness of order alpha and give the relations between statistical boundedness and lacunary statistical boundedness of order alpha.
Keywords: Density; statistical convergence; statistical boundedness; lacunary sequence